Active Matrix Electronic Skin Strain Sensor Based on Piezopotential‐Powered Graphene Transistors. (27th April 2015) - Sun, Qijun; Seung, Wanchul; Kim, Beom Joon; Seo, Soonmin; Kim, Sang‐Woo; Cho, Jeong Ho
<x xml:space="preserve">Abstract</x> A piezopotential‐powered active matrix strain sensor array based on a piezopotential‐gated graphene transistor (GT) is demonstrated using a piezoelectric polymer. The strain sensor based on the piezopotential‐gated GT exhibits excellent performance, including ultrahigh sensitivity (gauge factor = 389) and good durability (>3000 bending and releasing cycles) with a minimum detectable strain at 0.008%.